Eye moving desensitization dan reprocessing untuk mereduksi kecemasan menghadapi Covid-19 - Dian Renata; Hengki Satrianta (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2020)
Recently more events can appear traumatic effect even if it not treated, it will be post-traumatic stress disorder. Therefore, need the efforts to treat this problem. One of the way is using eye moving desensitization and reprocessing. This article focuses on treating post-traumatic stress disorder through eye moving desensitization and reprocessing. The aim of this article is to describe the general implementation of eye moving desensitization and reprocessing to treat post-traumatic stress disorder. Eye moving desensitization and reprocessing is able to be a technique to treat post-traumatic stress disorder. Finally, writer suggested for counseling practitioners in Indonesia can make this “unique therapy” as a therapy technique for post-traumatic stress disorder.